INDUSTRIAL SAFETY MONITORING IN THE CONDITIONS OF UNDERGROUND GOLD MINING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article substantiates the system of industrial safety monitoring for the objects of the industrial technical system in the underground development of gold deposits. Algorithms for solving industrial safety problems in intensive subsurface use are proposed, and the regulatory and legal aspects of monitoring the industrial safety of the natural-technical system in relation to mining facilities are presented.